Hahnemann’s Concept of Posology and its Utility (Advancements in Homeopathic Research, 2022)
The Homoeopathic Science is the Science of determining and understanding of dose as based on research into large number of factors. We have tried our sincere efforts & humble attempts to focus on concept of Posology.
Keywords: Posology.; homoeopathic; Medicine; chronic disease